Pengembangan E-Modul Bermuatan Sejarah Lokal di Sumpur Kudus untuk Siswa SMAN 5 Sijunjung - Sari, Yohana Karnama; Hastuti, Hera (Jurusan Sejarah FIS UNP, 2025)
This research is motivated by the limited teaching materials provided in schools, especially on local history material. This study aims to develop, determine the feasibility and determine the results of the practicality and effectiveness test of the use of e-modules containing local history for students of SMAN 5 Sijunjung. The local history taken in this study is the history of the arrival of Islam in Sumpur Kudus. This research method is Research and Development (R&D) using the ADDIE development model. The research instrument was compiled including a questionnaire sheet consisting of a material expert validation sheet, an e-module expert validation sheet, and a practicality sheet for teachers and students. The implementation of this e-module was carried out on 31 students of grade X phase E at SMAN 5 Sijunjung. The data analysis of this study used quantitative descriptive obtained from scale measurements, namely Likert scale. This research went through a series of stages, starting with a needs analysis involving teachers, curriculum, and students. Furthermore, the e-module development process was designed using the Canva application. In the feasibility test phase, the material received an average score of 3.72 and the media received a score of 3.34, both of which are in the very feasible category. The implementation of the e-module was evaluated through a practicality test, where teachers gave an average score of 3.7 and students received a score of 3.51, indicating that the e-module was very practical to use. In the final stage, the effectiveness of the e-module was analyzed through interviews with teachers and students. In addition, post-tests and pre-tests were also conducted on students, which confirmed that the e-module containing local history was effective as a learning resource for students.